Pengaruh Risiko Pembiayaan Akad Murabahah, Musyarakah, dan Mudharabah terhadap Profitabilitas BPRS di Indonesia Tahun 2011-2019 - Silvia Isfiyanti; Rozmita Dewi Yuniarti; Rumaisah Azizah Al Adawiyah (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2020)
Profitability is the ability of the company to generate profits to determine the company's financial performance. The development of Non Performing Financing at BPRS is in high ratio, besides that the development of Return on Assets fluctuates but tends to decline. This indicates the existence of problems faced by BPRS in maximizing the profit to be obtained. This study aims to determine the effect of Murabahah financing (NPF), Musyarakah financing (NPF), and Mudharabah financing (NPF) risks on BPRS Return on Assets (ROA) in Indonesia in 2011-2019. The research method that used is a quantitative method using multiple linear regression analysis. The results showed that the financing risk (NPF) of the Murabahah, Musyarakah, and Mudharabah effect on ROA. Partially, the risk of Murabahah financing results on it has a significant effect on ROA in a negative direction, while the risk of Musyarakah financing has no significant effect on ROA in a positive direction, besides the risk of Mudharabah financing has a significant and significant effect on ROA in a positive direction. The findings of this study produce implications whether the financing risk on the Murabahah, Musyarakah, and Mudharabah financing increases, the Return on Assets will decrease, and if it lefts unchecked will affect the financial performance of the company and the market share of Islamic banking.